ANALISIS EFEKTIFITAS PEMUNGUTAN PAJAK MELALUI LAYANAN SAMSAT DRIVE THRU (Studi Kasus Kantor Bersama Samsat Batu Kota) - Novia Rahmawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research purposes to determine the effectiveness of tax collection on SAMSAT Drive Thru services and to compare the revenue collection before and after the application of SAMSAT Drive Thru service. This research was conducted in KB SAMSAT of Batu City , using secondary data fiscal year 2009 through 2013. This quantitative research the effectiveness ratio and descriptive analyse used to describe the data and the percentage. The value of revenue efectiveness ratio show that SAMSAT drive thru service increase in revenue, this factors can be seen on the number of taxpayers of SAMSAT Drive Thru service, revenue, standard of services, and the satisfaction of the taxpayers. Based on the calculation of the ratio effectiveness and statistic descriptive analysis can be conclude that show that SAMSAT Drive Thru service at KB SAMSAT of Batu City has been very effective.Keywords: Effectiveness of Tax Collection, SAMSAT Drive Thru Service